Integration of Philosophical and Theoretical Paradigms in Developing an Adaptive Islamic Education Curriculum for the Modern Era - Ibrahim; Abdurrahmansyah; M. Sirozi; Afroza Yasmin Mitu (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
This study aims to analyze issues related to the integration of philosophical and theoretical paradigms in the development of an adaptive Islamic Religious Education (PAI) curriculum in the modern era. It employs a library research approach by collecting, analyzing, and synthesizing data from relevant literature, including books, journals, and policy documents. The analysis is conducted descriptively-analytically through content analysis to examine themes, concepts, and patterns concerning the integration of philosophy and theory in PAI curriculum development. The findings and discussion affirm that the integration of Islamic philosophical paradigms and modern educational theories in the development of the Islamic Religious Education curriculum constitutes a strategic foundation for curriculum renewal that is responsive to contemporary demands. The novelty of this study lies in the formulation of an integrative conceptual framework that positions Islamic philosophy grounded in the Qur’an and Hadith as the normative foundation for the formation of insan kamil, while synthesizing essentialism, progressivism, constructivism, and humanism as operational pedagogical approaches. Theoretically, this study advances PAI curriculum theory by shifting its orientation from a normative–ritualistic focus toward an adaptive, holistic, contextual, and transformative curriculum that emphasizes the strengthening of spiritual, moral, and social values, as well as 21st-century skills (4C). The main conceptual outcome of this research is an integrative–adaptive PAI curriculum model that requires alignment of institutional vision, reflective teacher competence, sustainable policy support, and the implementation of innovative, meaningful, and effective learning strategies for learners.